No Evidence of Hepatitis C Virus Infection in Individuals with Cardiovascular Disease in Mashhad - Shakeri Hoseinabad, Morteza; Aryan, Ehsan; Ghayour Mobarhan, Majid; Moohebati, Mohsen; Abolbashari, Samaneh; Gholoobi, Aida; Houshyar Chechaklou, Amin; Yaghoubi, Atieh; Meshkat, Mojtaba; Meshkat, Zahra (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Hepatitis C virus (HCV) infection is one of the leading causes of morbidity and mortality worldwide. It has been hypothesized that a number of bacteria and viruses might be involved in the pathogenesis of cardiovascular disease. The aim of this study was to define the prevalence of HCV in patients with cardiovascular disease in comparison with a control group. Methods: In this study, 281 individuals including 143 cardiovascular patients and 138 healthy controls were assessed for identification of HCV antibodies. The data collection was done between April 2016 and February 2017. The prevalence of HCV antibodies was determined by the enzyme-linked immunosorbent assay (ELISA) method. Results: There was no HCV infection in both patients with or without cardiovascular disease. There was a significant direct correlation between cardiovascular diseases and mean level of FPG (Fasting plasma glucose) (p<0.001). Also the Systolic and Diastolic blood pressures were significantly higher in the patients with cardiovascular disease (p<0.001 and p=0.005, respectively). Conclusion: The results of this study show that no evidence of HCV infection is found among a group of cardiovascular patients in the city of Mashhad. *Corresponding Author: Zahra Meshkat; Email: meshkatz@mums.ac.ir Please cite this article as: Shakeri Hoseinabad M, Aryan E, Ghayour Mobarhan M, Moohebati M, Abolbashari S, Gholoobi A, Houshyar Chechaklou A, Yaghoubi A, Meshkat M, Meshkat Z. No Evidence of Hepatitis C Virus Infection in Individuals with Cardiovascular Disease in Mashhad. Arch Med Lab Sci. 2021;7:1-5 (e13). https://doi.org/10.22037/amls.v7.33445